Transalpine dispersal: Italian barred grass snakes in southernmost Bavaria—This far but no further!. (20th April 2021) - Asztalos, Marika; Glaw, Frank; Franzen, Michael; Kindler, Carolin; Fritz, Uwe
Abstract: Based on 1031 samples of grass snakes from Central Europe, we examine the recently reported occurrence of the southern subspecies of the barred grass snake ( Natrix helvetica sicula ) in southern Bavaria, Germany. Using 13 microsatellite loci and mtDNA coding for the cytb gene and the partial ND4 gene plus adjacent tRNAs, we show that N. h. sicula is restricted to a few river valleys (Inn, Isar, Loisach) in southernmost Bavaria and adjacent Tyrol, Austria. At the widening of the river valleys into the pre‐Alpine plains, N .  h .  sicula hybridizes locally with the common grass snake ( Natrix natrix ) in a bimodal hybrid zone. Our study provides evidence that Central Europe was colonized by Natrix helvetica over two distinct immigration routes. In addition to the previously known western route of the nominotypical subspecies, leading to the colonization of the Rhine region, N .  h .  sicula crossed the Alps, most likely using the Brenner Pass and/or the Reschen Pass. Our study underlines that the Alps are not an impermeable biogeographic barrier, as often assumed. North of the Alps, the combination of geographic setting (occurrence of N .  h .  sicula in sheltered Alpine valleys) and population‐density‐dependent blocking of immigrants by the resident species ( N .  natrix ), acting in concert with intrinsic genetic factors, prevented the formation of a geographically more extended hybrid zone. Unlike N .  helvetica, the two subspecies of N .  natrix hybridize north of the Alps broadly, in accordance with their better genetic compatibility. Many populations of the resident Central European subspecies ( Natrix natrix natrix ) have been "genetically swamped" by Natrix natrix vulgaris immigrating from the Balkans. This led to the complete replacement of N .  n .  natrix by N .  n .  vulgaris in some regions, where today only the mtDNA of the nominotypical subspecies persists. Abstract : We genetically confirm that Natrix helvetica sicula crossed the Alps in the Holocene and occurs now in southern Bavaria (Germany) and Tyrol (Austria). North of the Alps, the combination of geographic setting, intrinsic genetic factors, and population‐density‐dependent blocking of immigrants by the resident species ( Natrix natrix ) prevented the formation of a geographically more extended hybrid zone between N .  h .  sicula and N .  natrix . In contrast, the two local subspecies of N .  natrix hybridize broadly north of the Alps.